A Different Kind of Outing: Training Counsellors to Work with Sexual Minority Clients - Alderson, Kevin G. (Canadian Journal of Counselling and Psychotherapy, 2007)
Past research indicates sexual minority training provided to graduate students of counselling psychology is minimal and inadequate (Bahr, Brish, & Croteau, 2000; Morrison & L’Heureux, 2001; Murphy, 1991). Graduates feel unprepared to work competently with sexual-minority individuals, yet Canadian and American Associations require their members to be knowledgeable about sexual orientation and to be competent in providing counselling services to diverse clientele. Results from a four-item questionnaire e-mailed to 14 Canadian universities suggested minimal training is offered to counselling graduate students concerning gay and lesbian psychology and counselling. Following a literature review, a flexible curriculum is suggested for counselling psychology graduate programs that conforms to theorized requirements for both multicultural competency and for effective lesbian, gay, and bisexual affirmative counselling practice.